Association Between PIP4K2A Polymorphisms and Acute Lymphoblastic Leukemia Susceptibility. Issue 18 (May 2016) - Liao, Fei; Yin, Dandan; Zhang, Yan; Hou, Qianqian; Zheng, Zhaoyue; Yang, Li; Shu, Yang; Xu, Heng; Li, Yu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Acute lymphoblastic leukemia (ALL) is one of the most common pediatric cancers in the world. Several single-nucleotide polymorphisms (SNPs) locating at PIP4K2A locus were identified to be associated with ALL susceptibility through genome-wide association studies, however, followed by inconsistent reports in replication studies. In this study, we conducted a meta-analysis to investigate the association status of the top independent SNPs (rs7088318 and rs4748793) with ALL susceptibility by combining the data from 6 independent studies, totally including 3508 cases and 12, 446 controls with multiethnic populations. Consistent association with ALL risk of both SNPs were observed (odds ratio [OR] 1.28 and 1.29, 95% confidence interval [CI] 1.20–1.36 and 1.19–1.40, respectively). Considering clinic characteristics, rs7088318 is more related to patients with African ancestry (OR 1.48, 95% CI 1.21–1.80) and hyperdiploid subtype (OR 1.42, 95% CI 1.25–1.61). Moreover, several SNPs (eg, rs45469096) were identified to be in high linage disequilibrium with rs7088318, and affected PIP4K2A expression in lymphocytes probably by altering the binding affinity of some transcriptional factors. In conclusion, we systematically investigated the relationship between SNPs at PIP4K2A locus and ALL susceptibility, and further found potential causal variant candidates, thus better elucidating the role of PIP4K2A gene in leukemogenesis.